Semisynthetic sensor proteins enable metabolic assays at the point of care - Yu, Qiuliyang; Xue, Lin; Hiblot, Julien; Griss, Rudolf; Fabritz, Sebastian; Roux, Clothilde; Binz, Pierre-Alain; Haas, Dorothea; Okun, Jürgen G.; Johnsson, Kai (Science, 2018)
A protein designed to sense metabolites - Many diseases cause characteristic changes in blood metabolites. Yu et al. describe a paper-based assay in which a chosen metabolite can be oxidized to generate reduced nicotinamide adenine dinucleotide phosphate (NADPH). Color changes in a designed NADPH sensor protein are then quantified by a digital camera. The sensor system successfully generated point-of-care measurements of phenylalanine, glucose, and glutamate. Concentrations of phenylalanine in the blood of phenylketonuria patients were analyzed within minutes with only half a microliter of blood. - Science, this issue p. 1122 - Monitoring metabolites at the point of care could improve the diagnosis and management of numerous diseases. Yet for most metabolites, such assays are not available. We introduce semisynthetic, light-emitting sensor proteins for use in paper-based metabolic assays. The metabolite is oxidized by nicotinamide adenine dinucleotide phosphate, and the sensor changes color in the presence of the reduced cofactor, enabling metabolite quantification with the use of a digital camera. The approach makes any metabolite that can be oxidized by the cofactor a candidate for quantitative point-of-care assays, as shown for phenylalanine, glucose, and glutamate. Phenylalanine blood levels of phenylketonuria patients were analyzed at the point of care within minutes with only 0.5 microliters of blood. Results were within 15% of those obtained with standard testing methods. - Sensor proteins allow a paper-based color-change assay of important metabolites, including phenylalanine. - Sensor proteins allow a paper-based color-change assay of important metabolites, including phenylalanine.
Gesehen am 05.03.2020